Allergic Contact Dermatitis to Topical Clindamycin in a Patient with Hidradenitis Suppurativa - Anja Pahlow Mose; Usamah Adwa; Cecilia Svedman (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)